On the reproductive biology of the talitrid amphipod Platorchestia monodi (Mateus et al.,1986) from the Shatt Al-Arab region, Basrah, Iraq - Salman, Salman D.; Hamzah, H. A.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
The life history and breeding activity of the supralittoral amphipod, Platorchestia monodi (Mateus et al. 1986) were studied. The amphipods were sampled from the Garmat-Ali region, Basrah, over the period from 26th August 1993-28th January 1995. Random samples were taken on a monthly basis. The amphipods were mostly abundant under drifted aquatic plants (wrack), which were providing food and shelter. Sexual maturity occurred in the males at a size of 5.25 mm and 5.0 mm in the females. Ovigerous females were found throughout the year. Mean egg size (0.75 mm) was increasing during the embryonic development. Mean brood size was ranging from 5-18 ova, and the fecundity was an exponential function of size of female. There was a preponderance of females (1.9:1) over males in the population. The population was polymodal throughout the entire sampling period. The life span of the males was 11-14 months, whereas that of the females was 15 months.